2023
DOI: 10.54434/candj.164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Minerals in COVID-19: An Umbrella Review

Claudine Van De Venter,
Cécile Konn,
Monica Doherty
et al.

Abstract: Background: This umbrella review aims to synthesize the existing literature on the preventive and therapeutic benefits of minerals zinc, selenium, iron, copper, magnesium, phosphorus, and calcium in the context of COVID-19 prevention and management. The objective is to highlight the clinical applicability and identify avenues of future research. Methods: A systematic search was conducted in PubMed and Google Scholar databases using predefined keywords for each mineral combined with COVID-19–related terms. Narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…The Task Force identified and produced six umbrella reviews encompassing herbal medicine 11 ; vitamins 12 ; minerals 13 ; nutraceuticals (quercetin, n-acetyl cysteine, omega-3 fish oil, melatonin, probiotics, and propolis) 14 ; diet and food 15 ; and movement, exercise and breathing. 16 As outlined in Table 1, the umbrella review started with 94 narrative reviews and 308 systematic reviews identified by the live review.…”
Section: Included Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Task Force identified and produced six umbrella reviews encompassing herbal medicine 11 ; vitamins 12 ; minerals 13 ; nutraceuticals (quercetin, n-acetyl cysteine, omega-3 fish oil, melatonin, probiotics, and propolis) 14 ; diet and food 15 ; and movement, exercise and breathing. 16 As outlined in Table 1, the umbrella review started with 94 narrative reviews and 308 systematic reviews identified by the live review.…”
Section: Included Reviewsmentioning
confidence: 99%
“…The umbrella reviews identified a range of important findings. The reviews by Murphy et al, 15 Remy, 12 and Van De Venter et al 13…”
Section: Summary Statementsmentioning
confidence: 99%